Can children influence policy? The contribution of working children's union's [i.e. unions] in tackling child labour : a case study of Bhima Sangha, Karnataka, India : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University - Nadikerianda, Poonacha (Massey University, 2009)
The high incidences of child labour across the globe commands worldwide attention and have given rise to a number of competing explanations. Broadly speaking, these explanations can be categorised under those factors, which focus on poverty and under-development, and those which focus on policy failure and poor implementation of educational services. However, in the debates of child labour, grossly neglected are the experiences and voices of working children. Giving children a voice and space to participate in debates surrounding child labour, has thrown up a whole range of questions, challenging common assumptions of childhood and the relationship between children and adults. By reviewing the body of literature on working children's movements, their involvement and contribution towards policies and decisions in the struggle against child labour, the following research provides pragmatic perspectives on the appropriateness and capability of children to participate in decision making processes and the importance of recognising working children's movements in the debates and dilemmas surrounding child labour.
Keywords: India Karnataka; Child labor; Labor unions; Law legislation